Toll-like receptor 4 and CD11b expressed on microglia coordinate eradication of Candida albicans cerebral mycosis - Wu, Yifan; Du, Shuqi; Bimler, Lynn H; Mauk, Kelsey E; Lortal, Léa; Kichik, Nessim; Griffiths, James S; Osicka, Radim; Song, Lizhen; Polsky, Katherine; Kasper, Lydia; Sebo, Peter; et al. (Cell reports, 2023)
The fungal pathogen Candida albicans is linked to chronic brain diseases such as Alzheimer's disease (AD), but the molecular basis of brain anti-Candida immunity remains unknown. We show that C. albicans enters the mouse brain from the blood and induces two neuroimmune sensing mechanisms involving secreted aspartic proteinases (Saps) and candidalysin. Saps disrupt tight junction proteins of the blood-brain barrier (BBB) to permit fungal brain invasion. Saps also hydrolyze amyloid precursor protein (APP) into amyloid β (Aβ)-like peptides that bind to Toll-like receptor 4 (TLR4) and promote fungal killing in vitro while candidalysin engages the integrin CD11b (Mac-1) on microglia. Recognition of Aβ-like peptides and candidalysin promotes fungal clearance from the brain, and disruption of candidalysin recognition through CD11b markedly prolongs C. albicans cerebral mycosis. Thus, C. albicans is cleared from the brain through innate immune mechanisms involving Saps, Aβ, candidalysin, and CD11b.
Keywords: secreted aspartic proteinase; blood-brain barrier; toll-like receptor 4; cerebral mycosis; fungální proteiny; microglia; antigeny CD11b; Toll-Like Receptor 4; Alzheimer Disease; Alzheimer’s disease; CP: Immunology; zvířata; Alzheimerova nemoc; amyloidní beta-protein; myši; Mice; Amyloid beta-Peptides; CD11b; Toll-like Receptor 4; Microglia; mikroglie; mykózy; CD11b Antigen; Candida albicans; Animals; Mycoses; amyloid beta; candidalysin; CP: Neuroscience; Fungal Proteins